Identification of Similarities Between Skin Lesions in Patients With Antisynthetase Syndrome and Skin Lesions in Patients With Dermatomyositis by Highly Multiplexed Imaging Mass Cytometry. Issue 5 (11th March 2022) - Patel, Jay; Ravishankar, Adarsh; Maddukuri, Spandana; Vazquez, Thomas; Grinnell, Madison; Werth, Victoria P.
Abstract : Objective: Antisynthetase syndrome (ASyS) and dermatomyositis (DM) are autoimmune disorders that overlap clinically. Given the presence of DM‐like skin lesions in ASyS patients, there is debate about whether ASyS is a distinct disease or a subclassification of DM. Recent studies identified differences in type I interferon (IFN) expression between ASyS and DM muscle and finger eruptions. This study was undertaken to elucidate similarities and differences in the pathogenesis of cutaneous disease in ASyS and DM at the single‐cell level. Methods: Five ASyS patients and 7 DM patients were recruited from a prospectively collected database of well‐characterized DM patients. ASyS patients were clinically confirmed as having ASyS according to the Connors et al criteria and the Solomon et al criteria and the presence of aminoacyl–transfer RNA synthetase antibodies. Immunophenotyping was conducted using immunofluorescence (IF) and imaging mass cytometry (IMC). Results: IF staining for MxA and IFNβ expression revealed up‐regulation of type I IFN in ASyS and DM samples compared to healthy control samples ( P < 0.05). IMC showed similar numbers of macrophages, T cells, B cells, and dendritic cells in ASyS and DM samples, with no differences in counts ( P > 0.05), but an increase in myeloid dendritic cell percentage in DM samples ( P < 0.05). Key type I IFN, cytokine, and JAK/STAT pathways were similarly expressed in both ASyS and DM ( P > 0.05). At the single‐cell level, macrophages positive for phosphorylated stimulator of IFN genes in ASyS samples expressed increased levels of tumor necrosis factor, interluekin‐17 (IL‐17), and IFNβ ( P < 0.001). Conclusion: IMC is a powerful tool that identifies a role for the type I IFN system in DM‐like skin lesions in ASyS and DM with some differences at the cellular level, but overall significant overlap, supporting similar therapeutic decision making.